ChemInform Abstract: C—H Alkenylations with Alkenyl Acetates, Phosphates, Carbonates, and Carbamates by Cobalt Catalysis at 23 °C. Issue 38 (3rd September 2015) - Moselage, Marc; Sauermann, Nicolas; Richter, Sven C.; Ackermann, Lutz
Abstract The regioselective C‐H alkenylation of N‐(2‐pyrimidyl) or N‐(2‐pyridyl) substituted indoles using a variety of O‐substituted cyclohexanol derivatives in the presence of CoI2 and a NHC‐carbene is presented.